Comparison of methods for the microbiological diagnosis of totally implantable venous access port-related infections. Issue 11 (16th November 2020) - Kaya, Esingül; Tollapi, Lara; Pastore, Alberto; Aringhieri, Giacomo; Maisetta, Giuseppantonio; Barnini, Simona; Paolicchi, Adriana; Batoni, Giovanna; Esin, Semih
Abstract : Introduction . Totally implanted venous access ports (TIVAPs) are widely used in patients receiving long-term chemotherapy but may lead to serious complications such as catheter-related bloodstream infections (CRBSIs). Diagnosis of CRBSI requires catheter culture, but there is no consensus on microbiological culture methods to be adopted. Aim . To compare three different procedures to recover bacterial cells from colonized catheters and to determine which section of the TIVAP (i.e. tip, septum, reservoir) is the probable source of infection. To investigate the correlation between blood culture results and TIVAP culture in order to get further evidence about the utility of differential time to positivity (DTP) as a diagnostic tool before TIVAP removal. Hypothesis/Gap statement. Comparisons of different diagnostic procedures for catheter culture have been rarely reported for TIVAPs. We hypothesized that the optimization of methods to recover micro-organisms from different parts of TIVAPs may help to decrease the number of false-negative results in the diagnosis of TIVAP-related bloodstream infections. Methodology . A total of 53 TIVAPs removed because of suspected infection ( n =36) or end of use ( n =17) were evaluated. The reservoir, the septum and the catheter tip were separated and subjected to different treatments for the recovery of adherent micro-organisms: (a) flushing of the catheter lumen, (b) sonication and flushing, (c) treatment with dithiothreitol and flushing. The three methods were also evaluated in an in vitro catheter infection model with Staphylococcus epidermidis . Culture results were compared to those obtained from paired blood cultures drawn from TIVAP and peripheral vein and to the relative DTP. Results . The results obtained demonstrated that vigorous flushing/vortexing of the catheter lumen/septum, allows the recovery of a number of micro-organisms comparable to that of more complex procedures such as sonication or chemical treatment. Among 24 positive TIVAP-cultures, nine were tip-culture negative, whereas the corresponding reservoirs and septa were culture positive. A good correlation was observed between DTP and TIVAP cultures ( P <0.001). Conclusions . The results support the evidence that sending the port reservoir in addition to the catheter tip to the microbiology laboratory may increase the sensitivity and the accuracy of CRBSI diagnosis. Moreover, when a TIVAP-related infection is suspected, DTP is a useful diagnostic tool to decide between device removal or a more conservative approach.